Fatores associados à mortalidade hospitalar após trauma cranioencefálico moderado e grave antes e durante a pandemia de COVID-19 - Assis, Esther da Silva Tavares (2023)
Introduction: Traumatic brain injury (TBI) is a silent epidemic that affects working-age young people all over the world. TBI is responsible for a considerable number of deaths and temporary and permanent sequelae. Early treatment and identification of lifethreatening factors in TBI patients are extensively studied worldwide. However, the mortality and outcome pattern of TBI patients after the COVID-19 pandemic is unknown. In view of the above, it is necessary to know the factors associated with hospital mortality of patients with moderate and severe TBI before and during the COVID-19 pandemic. Objective: To assess clinical and sociodemographic factors associated with in-hospital mortality after moderate and severe TBI before and during the COVID-19 pandemic. Method: This is a retrospective cohort study with data collected from the physical records of patients who were admitted to the service from March 11, 2019, to March 11, 2021, at the Emergency Hospital of the State of Sergipe “Governador João Alves Filho” (HUSE) in the city of Aracaju - Sergipe. The study included patients with moderate and severe blunt TBI, aged ≥ 18 years, who were admitted within six hours after the traumatic event. Sociodemographic and clinical characteristics of patients, severity of trauma and TBI, results of laboratory tests, outcome of death or discharge were collected from the medical records. The MantelHaenszel association test for categorical variables and the ART-ANOVA (Aligned Ranked Transform Analysis of Variance) for continuous variables were applied to investigate differences between the results before and during the pandemic. Results: The casuistry consisted of 94 patients, almost all (98.9%) male, with a median age of 40.5 years, 48.88% involved in motorcycle accidents, 30.8% suffered accidents in the night and early morning. Significant statistical differences were found in the period before and during the pandemic between patients who suffered transport accidents (p=0.029), falls (p=0.033), were sedated on admission (p=0.021), intubated on admission (p=0.005), presented fracture (p=0.042), and presented subdural hemorrhage (p=0.010). Regarding the factors associated with the outcome of hospital death, comparing patients with moderate and severe TBI before and during the pandemic, the following factors were found: use of vasoactive drugs (p=0.025), cardiovascular alterations (p=0.046), hyperglycemia (p=0.001), cerebral contusion (p=0.035), temperature on admission (p=0.040), and the Revised Trauma Score (p= 0.008). No statistically significant difference was observed in patients’ mortality before and during the COVID-19 pandemic. Conclusion: The study revealed mortality of moderate and severe TBI patients. The comparative analysis of the outcome of death between patients with moderate and severe TBI, both before and during the pandemic, showed statistically significant differences related to the use of vasoactive drugs, presence of cardiovascular alterations, hyperglycemia, cerebral contusion, temperature on admission and severity assessed by the RTS score.